Targeted inhibition of macrophage STING signaling alleviates inflammatory injury and ventricular remodeling in acute myocardial infarction - Huan Yao; Qingman He; Shujun Wei; Li Xiang; Yuanyuan Luo; Cong Huang; Weiwei Liu; Chuan Zheng; Xueping Li; Yongxiang Gao (Acta Pharmaceutica Sinica B)
Mitochondrial DNA (mtDNA) acts as a damage-associated molecular pattern to activate the stimulator of interferon genes (STING) signaling in macrophages, promoting tissue inflammation. However, its role in acute myocardial infarction (AMI) remains unclear. Macrophage-specific Sting1 knockout mice were used to validate STING's pathological role in AMI. Cardiac and liver mtDNA were used to activate macrophages in co-culture systems with cardiomyocytes to assess fibrosis and hypertrophy. Panaxatriol saponin (PTS) was tested for its ability to block mtDNA-driven macrophage activation and subsequent cardiomyocyte damage. STING–PTS binding ability was analyzed. AMI rats received PTS to evaluate its effects on myocardial inflammation and ventricular remodeling. In vivo, macrophage-specific Sting1 knockout reduced myocardial inflammation and injury after AMI. In vitro, mtDNA-activated macrophages induced cardiomyocyte fibrosis and hypertrophy through STING signaling. PTS suppressed mtDNA-driven macrophage activation by directly binding STING, thereby blocking inflammatory cascades. In AMI rats, PTS treatment attenuated acute inflammation and reversed ventricular remodeling. These findings establish the mtDNA–STING axis in macrophages as a critical driver of post-AMI inflammation and identify pharmacological STING inhibition with PTS as a promising therapeutic strategy. The study bridges genetic validation with translational applications, highlighting macrophage STING as a novel target for ischemic heart disease management.